What a Performance! Madonna, Montaigne, Cyrano and Existential Anguish (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
This is less a 'paper' than an essay; and as such is merely an 'attempt,' a 'trying,' moving towards inevitable incompleteness and not knowing. I attempt a consideration of a range of artistic and philosophical responses to the significant moment(s) of anguish and loss in human experience. Along the way I try out an engagement with concepts of being/becoming, uncertainty, wonder and performance, considering their value in our Sisyphean attempt to grasp the elusive.
Keywords: Madonna; Montaigne; Eliot; Barnes; dance; performance; wonder; temporality; grief; elusive.